Evaluation of optical density of rats tibiae bone repair treated with rofecoxib. Pilot study - Gabriela Alessandra da Cruz; Mari Eli Leonelli de Moraes; Luiz César de Moraes; Rosilene Fernandes da Rocha; Ivan Balducci (Brazilian Dental Science)
The aim of this study was to evaluate the influence of rofecoxib on bone repair process in tibiae of rats by means of analysis of gray levels acquired by digital optical density. Ten Wistar rats were assigned to two groups: an untreated control group and a group treated with rofecoxib. The experimental procedures comprised the following stages: general anesthesia, preparation of unicortical bone defect on the left tibiae of each rat, medication with rofecoxib and radiographic examination. Digital radiographic images were taken using Visualix GX-S-HDITM digital sensor, an X-ray equipment. Radiographics were taken at baseline, 7, 14, 21 and 30 days postoperatively and the gray levels were evaluated using the Vix winTM 1.4 system of the region of interest (ROI). The mean values of ROI readings were analyzed statistically by repeated measures ANOVA with significance level of 5%. There were no statistically significant differences among gray levels between rofecoxib and control groups (p=0.2429), but there were statistically significant differences between times baseline, 7, 14, 21 and 30 in both groups (p=0001). The findings of this study suggest that no influence was found when rofecoxib was used in bone tibiae repair after 30 days post-treatment.